Liquid–Liquid Extraction of Formic Acid with 2‑Methyltetrahydrofuran: Experiments, Process Modeling, and Economics - Laitinen, Antero T; Parsana, Vyomesh M; Jauhiainen, Olli; Huotari, Marco; van den Broeke, Leo J. P; de Jong, Wiebren; Vlugt, Thijs J. H; Ramdin, Mahinder (Industrial & engineering chemistry research, 2021)
Formic acid (FA) is an interesting hydrogen (H2) and carbon monoxide (CO) carrier that can be produced by the electrochemical reduction of carbon dioxide (CO2) using renewable energy. The separation of FA from water is challenging due to the strong (cross)association of the components and the presence of a high boiling azeotrope. For the separation of dilute FA solutions, liquid–liquid extraction is preferred over conventional distillation because distilling large amounts of water is very energy-intensive. In this study, we use 2-methyltetrahydrofuran (2-MTHF) to extract FA from the CO2 electrolysis process, which typically contains <20 wt % of FA. Vapor–liquid equilibrium (VLE) data of the binary system 2-MTHF–FA and liquid–liquid equilibrium (LLE) data of the ternary system 2-MTHF–FA–water are obtained. Continuous extraction and distillation experiments are performed to test the extraction power and recovery of 2-MTHF from the extract. The VLE and LLE data are used to design a hybrid extraction and distillation process to produce a commercial grade product (85 wt % of FA). A detailed economic analysis of this hybrid extraction–distillation process is presented and compared with the existing FA separation methods. It is shown that 2-MTHF is a cost-effective solvent for FA extraction from dilute streams (<20 wt % FA).